Lithium ion battery electrolyte and application thereof
By using specific additives in the lithium-ion battery electrolyte, the problem of insufficient fast charging rate and discharge capacity of lithium-ion batteries under low temperature conditions is solved, and the efficient fast charging and low-temperature performance of the battery is improved, while enhancing the safety of the battery.
Patent Information
- Application Number
- CN202411697418.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-11-25
AI Technical Summary
Lithium-ion batteries have insufficient fast charge rate and discharge capacity under low temperature conditions, and the electron conductivity and ion diffusion coefficient of the positive electrode active material with phosphate structure are low, which limits the high and low temperature performance and safety of the battery.
A lithium-ion battery electrolyte is used, which comprises a non-aqueous solvent, a lithium salt and a specific additive, including a first additive and a second additive. The first additive has high oxidation resistance and high dielectric constant, and can be oxidized and open-loop polymerized on the positive electrode side to form a film, reducing the viscosity of the electrolyte and improving the conductivity. The second additive is a boron-containing compound that can be adsorbed on the surface of the electrode material and improves the ability to conduct lithium ions.
Effectively suppress gas production, improve the fast charging and low-temperature discharge performance of lithium-ion batteries, reduce DC impedance, reduce the loss of active lithium, and improve the low-temperature lithium-ion window to enhance the high- and low-temperature performance and safety performance of the battery.
Smart Images

Figure CN119542535A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of power batteries, and in particular to a lithium-ion battery electrolyte and applications thereof. Background Art
[0002] As lithium-ion secondary batteries are increasingly used in power tools, electric vehicles and other fields, people are pursuing longer driving ranges while trying to achieve the same volume design, with the highest cell capacity possible. In some special application areas, lithium-ion batteries are required to cope with more severe weather conditions and take into account high and low temperature performance over a wider temperature range. In practical applications, carbonate solvent systems generally have problems such as high viscosity, poor fluidity, low ionic conductivity and low membrane wetting ability, which severely limit the system's high-rate discharge capability under low temperature conditions.
[0003] Phosphate-structured cathode active materials have the advantages of high energy density, complete crystal structure, relatively uniform particle distribution, good thermal stability and high safety. They meet the requirements of high safety and high and low temperature performance with a wider temperature range, and are widely used in electric vehicles, energy storage systems, power tools and other modules. However, phosphate-structured cathode active materials have the defects of low intrinsic electronic conductivity and low ion diffusion coefficient, and the fast charge rate and low-temperature discharge capability of the phosphate system need to be further improved. Summary of the invention
[0004] The present invention proposes a lithium ion battery electrolyte and application thereof. The lithium ion battery electrolyte and application thereof provided by the present invention can effectively inhibit gas production, improve the fast charging performance of the lithium ion battery, enhance the high and low temperature performance of the battery, and improve the safety performance of the battery.
[0005] In order to solve the above technical problems, the present invention provides a lithium ion battery electrolyte, comprising at least the following components:
[0006] Non-aqueous solvents;
[0007] lithium salts; and
[0008] Additives, the additives include a first additive and a second additive, the first additive has a structural formula of Formula A, and the second additive is selected from a compound having a structural formula of Formula B1 or Formula B2;
[0009]
[0010] Wherein, n1 and n2 are each independently any natural number from 1 to 3, and R1, R2, R3, R4, and R5 are each independently selected from -H, -F, C 1~6 Alkyl, C 1~6 Alkoxy, C 2~6 Alkenyl, C 2~6Alkenyloxy, C 2~10 Alkynyl, C 2~10 Alkynyloxy, C 3~8 Cycloalkyl, C 3~8 Epoxyalkyl, C 6~12 Aryl, C 6~12 heteroaryl or carbonyl, trifluoromethyl, and C 2~6 Any one or a combination of ester groups.
[0011] In one embodiment of the present invention, at least one of R1 and R2 includes C 2~6 Alkenyl, C 2~10 Alkynyl, C 1~6 Alkoxy, C 2~6 Any one or a combination of ester group or -F.
[0012] In one embodiment of the present invention, the first additive is selected from any one or a combination of the following compounds:
[0013]
[0014] In one embodiment of the present invention, the second additive is selected from any one or a combination of the following compounds:
[0015]
[0016]
[0017] In one embodiment of the present invention, the content of the first additive in the electrolyte is 0.5 wt % to 20 wt %.
[0018] In one embodiment of the present invention, the content of the second additive in the electrolyte is 0.5 wt % to 5 wt %.
[0019] In one embodiment of the present invention, the additive further includes a third additive, and the third additive is selected from at least one or more combinations of ethylene carbonate, 1,3-propane sultone, 1,3-propylene sultone, 2,4-butane sultone, methylene disulfonate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorophosphate, lithium difluorobisoxalatophosphate or vinyl sulfate.
[0020] In one embodiment of the present invention, the non-aqueous solvent is selected from at least one or more of ethylene carbonate, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, propylene carbonate, ethyl acetate, methyl acetate, ethyl formate, propyl formate, propyl acetate, methyl propionate, ethyl propionate or propyl propionate.
[0021] In one embodiment of the present invention, the lithium salt is selected from at least one or more of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium perchlorate, lithium hexafluoroarsenate and lithium tetrafluoroborate, lithium bis(oxalato)borate or lithium difluorooxalatoborate, and the content of the lithium salt in the electrolyte is 5wt% to 25wt%.
[0022] The present invention also provides a lithium ion battery, comprising:
[0023] A positive electrode plate, wherein the positive electrode plate includes a lithium supplement, and the lithium supplement includes one or more of Li2NiO2, Li6CoO4 or Li5FeO4;
[0024] Negative electrode;
[0025] A diaphragm, disposed between the positive electrode sheet and the negative electrode sheet;
[0026] The electrolyte is selected from the lithium-ion battery electrolyte described above.
[0027] In one embodiment of the present invention, the positive electrode plate includes a positive electrode active material, and the positive electrode active material includes at least one or more of lithium iron phosphate, a composite material of lithium iron phosphate and carbon, lithium manganese phosphate, a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon.
[0028] The present invention also provides an electronic device, comprising the lithium-ion battery described above.
[0029] In summary, the present invention proposes a lithium-ion battery electrolyte and its application. Through the combined use of a first additive and a second additive, the oxidation side reaction at the solid-liquid interface can be reduced, the stability of the electrochemical window can be improved, the gas production can be effectively suppressed, the viscosity of the electrolyte can be reduced, and the fast charging performance and low-temperature discharge performance of the lithium-ion battery can be improved. The DC impedance of the lithium-ion battery can be reduced, the loss of active lithium can be reduced, and the low-temperature lithium precipitation window can be improved. The stability of the interface film can be improved, thereby improving the electrochemical performance. The charge and discharge efficiency and energy density of the lithium-ion battery can be improved, the high and low temperature performance of the battery can be enhanced, and the safety performance of the battery can be improved. DETAILED DESCRIPTION
[0030] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.
[0031] It should be understood that the present invention can be implemented in different forms and should not be interpreted as limited to the embodiments set forth herein. On the contrary, these embodiments are provided to make the disclosure thorough and complete and to fully convey the scope of the present invention to those skilled in the art.
[0032] The technical scheme of the present invention is further described in detail below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0033] The present invention provides a lithium ion battery electrolyte, comprising at least a non-aqueous solvent, a lithium salt and an additive, wherein the additive comprises a first additive and a second additive, the first additive has a structural formula of formula A, and the second additive is selected from a compound having a structural formula of formula B1 or formula B2;
[0034]
[0035] Wherein, n1 and n2 are each independently any natural number from 1 to 3, and R1, R2, R3, R4, and R5 are each independently selected from -H, -F, C 1~6 Alkyl, C 1~6 Alkoxy, C 2~6 Alkenyl, C 2~6 Alkenyloxy, C 2~10 Alkynyl, C 2~10 Alkynyloxy, C 3~8 Cycloalkyl, C 3~8 Epoxyalkyl, C 6~12 Aryl, C 6~12 heteroaryl or carbonyl, trifluoromethyl, and C 2~6 In one embodiment of the present invention, at least one of R1 and R2 includes C 2~6 Alkenyl, C 2~10 Alkynyl, C 1~6 Alkoxy, C 2~6Any one or a combination of several of ester group or -F. Among them, the first additive has high oxidation resistance and stability, can be oxidized and polymerized to form a film on the positive electrode side, and has a high dielectric constant. It can replace part of the ethylene carbonate solvent as a solvent to keep the overall electrolyte conductivity at a high level, and can reduce the cyclic ethylene carbonate. The active oxygen oxidation decomposition released by the lithium supplement in the positive electrode plate can reduce the oxidative decomposition of the active oxygen released by the lithium supplement in the positive electrode plate, that is, it has the advantages of less oxidation side reactions at the solid-liquid interface and high electrochemical window stability. It can effectively inhibit gas production, reduce the viscosity of the electrolyte, and improve the fast charging performance and low-temperature discharge performance of lithium-ion batteries. The second additive is a boron-containing compound, which is more easily adsorbed on the residual functional groups on the surface of the electrode material. After the film is formed, the interface film contains more lithium borate, lithium fluoride and lithium carbonate substances, which further improves the ability to conduct lithium ions. The second additive and the first additive are used in combination to reduce the direct current resistance (DCR) of lithium-ion batteries, inhibit the gas production caused by the lithium supplement, reduce the loss of active lithium, and improve the low-temperature lithium precipitation window.
[0036] In one embodiment of the present invention, the first additive is selected from any one or a combination of the following compounds:
[0037]
[0038] In one embodiment of the present invention, the first additive is selected from any one or more of compound A-2, compound A-3, compound A-4 or compound A-5. Since these compounds are 5-membered ring or 6-membered ring structures, the ring structure has high tension and is easier to open the ring to form a film. At the same time, the ortho position of the unsaturated functional group includes a fluorine-containing substituent, which is easier to undergo an elimination reaction to produce a LiF-rich interface film, thereby improving the stability of the interface film and thus improving the electrochemical performance.
[0039] In one embodiment of the present invention, the second additive is selected from any one or a combination of the following compounds:
[0040]
[0041] In one embodiment of the present invention, the second additive is selected from any one or more of compound B-2, compound B-4 or compound B-5. Since the pyridine compounds substituted with fluorine atoms at the N-ortho position in the structures of these compounds have good film-forming properties, the performance of low-temperature interface lithium deposition of lithium-ion batteries is improved.
[0042] In one embodiment of the present invention, the content of the first additive in the electrolyte is 0.5wt% to 5wt%, and for example, 2wt% to 10wt%. The content of the second additive in the electrolyte is 0.5wt% to 20wt%, and for example, 1wt% to 3wt%. If the content of the first additive is too low, the conductivity of the electrolyte is low, the DC impedance is large, and the quality of the interface film formed is poor, and the low-temperature interface lithium precipitation performance is poor. As the content of the first additive increases, the conductivity of the electrolyte increases, the quality of the formed interface film is improved, the DC impedance is reduced, and the low-temperature performance and gas production performance of the lithium-ion battery are improved. If the content of the second additive is too low, the improvement of the DC impedance is not obvious. If the content of the second additive is too high, the reduction of the interface impedance and the improvement of the low-temperature lithium precipitation of the lithium-ion battery reach the threshold. Therefore, the content of the first additive and the second additive is controlled so that the gas production performance, low-temperature performance, fast charging performance and low-temperature discharge performance of the lithium-ion battery are within a preferred range.
[0043] In one embodiment of the present invention, the additive further includes a third additive, the third additive is selected from at least one or more combinations of film-forming additives such as vinylene carbonate (EC), 1,3-propane sultone (PS), 1,3-propylene sultone (PST), 2,4-butanesultone (2,4-Butanesultone), methylene methanedisulfonate (MMDS), lithium difluorooxalatoborate (LiODFB), lithium dioxalatoborate (LiBOB), lithium difluorophosphate (LiDFP), lithium difluorobis(oxalatophosphate) (LiDFOP) or vinyl sulfate (1,3,2-Dioxathiolane2,2-dioxide, DTD), and the content of the third additive in the electrolyte is 0.1wt% to 5wt%. In one embodiment of the present invention, the third additive is, for example, selected from any one or a combination of 0.02wt% to 5wt% of vinylene carbonate, 0.02wt% to 3wt% of 1,3-propane sultone, 0.02wt% to 3wt% of 1,3-propylene sultone, 0.02wt% to 3wt% of 2,4-butane sultone, 0.02wt% to 3wt% of methylene disulfonate, 0.02wt% to 3wt% of lithium difluorooxalatoborate, 0.02wt% to 3wt% of lithium dioxalatoborate, 0.02wt% to 3wt% of lithium difluorophosphate, 0.02wt% to 3wt% of lithium difluorobisoxalatophosphate, or 0.02wt% to 3wt% of vinyl sulfate. The third additive can cooperate with the first additive and the second additive to further improve the integrity and density of the interface film and improve the cycle performance and safety performance of the lithium-ion battery.
[0044] In one embodiment of the present invention, the lithium salt is selected from any one or more of lithium hexafluorophosphate (LiPF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium tetrafluoroborate (LiBF4), lithium bis(oxalate)borate or lithium bis(fluorooxalate)borate, and the content of the lithium salt in the electrolyte is 5wt% to 25wt%, and for example, 10wt% to 15wt%. In one embodiment of the present invention, the lithium salt is selected from lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide to improve the charge and discharge efficiency and energy density of the lithium ion battery, enhance the high and low temperature performance of the battery, and improve the safety performance of the battery.
[0045] In one embodiment of the present invention, the non-aqueous solvent includes, for example, at least one or more combinations of ethylene carbonate, dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), propylene carbonate (PC), ethyl acetate (EA), methyl acetate (MA), ethyl formate (MEE), propyl formate (PF), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP) or n-propyl propionate (PP). Among them, ethylene carbonate and propylene carbonate are cyclic carbonates, and the rest are linear ester solvents.
[0046] In one embodiment of the present invention, when preparing the electrolyte, in a glove box with an inert gas atmosphere such as argon gas with a moisture content and an oxygen content less than or equal to 0.1 ppm, the non-aqueous solvent is mixed uniformly according to the mass ratio, and the fully dried lithium salt is added to the non-aqueous solvent, and an additive is added to prepare a lithium ion battery electrolyte. The content described in this application is the weight percentage calculated based on the total weight of the electrolyte.
[0047] The present invention proposes a lithium-ion battery, which includes a shell and a bare cell arranged in the shell, and the bare cell includes a positive electrode sheet, a separator and a negative electrode sheet. The separator is placed between the positive and negative electrode sheets to prevent the positive and negative electrodes from short-circuiting, so that lithium ions can pass through. The positive electrode sheet, the separator and the negative electrode sheet are stacked in sequence to ensure that a separator is provided between any positive electrode sheet and any negative electrode sheet, and a multi-layer laminate is obtained by winding or folding, and is loaded into a battery shell as a bare cell. Finally, an electrolyte is injected into the shell once or multiple times so that the bare cell is completely immersed in the electrolyte. The electrolyte is, for example, selected from the above-mentioned electrolytes, and plays a role in conducting ions between the positive and negative electrode sheets. In one embodiment of the present invention, the lithium-ion battery is, for example, a secondary battery, and the secondary battery is, for example, a soft-pack battery, a square shell battery or a cylindrical battery, etc. The present invention does not specifically limit the type of lithium-ion battery.
[0048] In an embodiment of the present invention, the positive electrode sheet includes a positive electrode current collector and a positive electrode active layer coated at least on one surface of the positive electrode current collector. Among them, the positive electrode current collector is, for example, a metal foil or a composite current collector, etc. The metal foil is, for example, a foil material formed after surface treatment of nickel, nickel alloy, titanium, titanium alloy, aluminum, aluminum alloy, silver, silver alloy, or stainless steel, etc. The composite current collector, for example, includes a polymer material base layer and a metal layer formed at least on one surface of the polymer material base layer. Among them, the material of the polymer material base layer is, for example, selected from at least one of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), or polyethylene (PE), etc. The material of the metal layer is, for example, selected from at least one of aluminum, aluminum alloy, nickel, nickel alloy, silver, silver alloy, or titanium alloy, etc.
[0049] In an embodiment of the present invention, the positive electrode active layer includes a positive electrode active material, a binder, a conductive agent, etc. Among them, the positive electrode active material, for example, includes at least one or more of phosphate materials such as lithium iron phosphate, a composite material of lithium iron phosphate and carbon, lithium manganese phosphate, a composite material of lithium manganese phosphate and carbon, lithium manganese iron phosphate, and a composite material of lithium manganese iron phosphate and carbon, etc., to improve the safety, cycle performance, and temperature adaptability of the lithium-ion battery, etc. Among them, the general formula of lithium manganese iron phosphate is LiMn x Fe 1-x PO4, and the value range of x is 0 < x < 1. The binder is, for example, selected from any one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), ethylene-tetrafluoroethylene copolymer (ETFE), vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer (TFE-HFP-VDF), or tetrafluoroethylene-hexafluoropropylene copolymer (FEP), etc. The conductive agent is, for example, selected from any one or more of conductive carbon black (Super P), acetylene black, or Ketjen black, etc.
[0050] In an embodiment of the present invention, the positive electrode active layer further includes a lithium supplement agent, and the lithium supplement agent includes one or more of Li2NiO2, Li6CoO4, or Li5FeO4, etc., to increase the battery capacity, improve the cycle stability, slow down the consumption of SEI film formation, and optimize the battery life. In the positive electrode active layer, the mass ratio of the positive electrode active material, the lithium supplement agent, the conductive agent, and the binder is, for example, (92 - 97):(1 - 2):(1 - 3):(1 - 3).
[0051] In one embodiment of the present invention, the positive electrode active material is, for example, lithium iron phosphate, the lithium supplement agent is, for example, selected from Li5FeO4, the binder is, for example, selected from polyvinylidene fluoride, and the conductive agent is, for example, selected from acetylene black. After the positive electrode active material, the lithium supplement agent, the conductive agent and the binder are mixed in a mass ratio of, for example, 95.7:1.5:1:1.8, an organic solvent is added, and the system is stirred under the action of a vacuum mixer until it is uniform to obtain a positive electrode slurry. Among them, the organic solvent is, for example, selected from N-methylpyrrolidone (NMP). The positive electrode slurry is evenly coated on an aluminum foil, and then transferred to an oven for drying after drying at room temperature, and the positive electrode sheet is obtained through cold pressing, trimming, cutting and striping. In other embodiments, the positive electrode sheet can also be obtained by any other method of forming a positive electrode sheet.
[0052] In one embodiment of the present invention, the negative electrode plate includes, for example, a negative electrode current collector and a negative electrode active layer coated on at least one surface of the negative electrode current collector. The negative electrode current collector is, for example, a metal foil or a composite current collector, the metal foil is, for example, a copper foil, and the composite current collector includes, for example, a polymer material base layer and a metal layer formed on at least one surface of the polymer material base layer. The material of the polymer material base layer is, for example, selected from at least one of PP, PET, PBT, PS or PE, and the material of the metal layer is, for example, selected from at least one of copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver or silver alloy.
[0053] In one embodiment of the present invention, the negative electrode active layer includes a negative electrode active material, a conductive agent, a binder and a thickener. Among them, the negative electrode active material includes, for example, any one or more combinations of artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials or lithium titanate. Among them, the silicon-based material includes, for example, one or more of elemental silicon, silicon-oxygen compounds, silicon-carbon composites, silicon-nitrogen composites or silicon alloys, and the tin-based material includes, for example, one or more of elemental tin, sacrificial oxygen compounds or tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries can also be used. These negative electrode active materials can be used alone or in combination of two or more.
[0054] In one embodiment of the present invention, the binder is selected from at least one of styrene butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylic amide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) or carboxymethyl chitosan (CMCS). The thickener is selected from carboxymethyl cellulose sodium (CMC-Na), etc. The conductive agent is selected from any one or more of superconducting carbon, acetylene black, carbon black, ketjen black, carbon dots, carbon nanotubes, graphene or carbon nanofibers. The mass ratio of the negative electrode active material, the conductive agent, the binder, and the thickener in the negative electrode active layer is, for example, (94-97):(1-2):(1-2):(1-2).
[0055] In one embodiment of the present invention, the negative electrode active material is selected from graphite and silicon-carbon composite, and the mass ratio of silicon-carbon composite to graphite is, for example, 2:98 to 5:95. By adding a small amount of silicon-carbon composite, the thickness of the negative electrode active layer can be reduced, the fast charging window of the lithium-ion battery can be improved, and the impact on the first discharge capacity can be reduced. The conductive agent is selected from conductive carbon black, the thickener is selected from sodium carboxymethyl cellulose, and the binder is selected from styrene-butadiene rubber. In one embodiment of the present invention, the negative electrode active material, the conductive agent, the thickener and the binder are mixed, for example, in a mass ratio of 96.5:1:1:1.5, deionized water is added, and the mixture is mixed evenly under the action of a vacuum mixer to obtain a negative electrode slurry, and the negative electrode slurry is coated on a copper foil, and then transferred to an oven for drying after drying at room temperature, and the negative electrode sheet is obtained through cold pressing, trimming, cutting and stripping. In other embodiments, the negative electrode sheet can also be obtained by any other method of forming the negative electrode sheet.
[0056] In one embodiment of the present invention, the diaphragm is, for example, a ceramic diaphragm, a polymer diaphragm, a non-woven fabric or an inorganic-organic composite diaphragm, including but not limited to a single-layer polypropylene film (Polypropylene, PP), a single-layer polyethylene film (Polyethylene, PE), a double-layer PP / PE film, a double-layer PP / PP film and a three-layer PP / PE / PP film.
[0057] In one embodiment of the present invention, the positive electrode sheet, the separator, and the negative electrode sheet are placed in sequence, so that the separator is located between the positive electrode sheet and the negative electrode sheet to play an isolating role, and a bare cell is obtained by winding or stacking. The bare cell is placed in a shell, dried, injected with electrolyte, and sealed, and at least vacuum packaging, standing, forming, and shaping are performed to obtain a lithium-ion battery.
[0058] Hereinafter, the present invention will be explained in more detail by citing examples, which should not be construed as limiting. Appropriate modifications may be made within the scope consistent with the gist of the present invention, all of which fall within the technical scope of the present invention.
[0059] Example 1
[0060] Preparation of electrolyte: In an argon glove box with an oxygen content of 0.1ppm and a water content of 0.1ppm, EC, EMC, DMC and compound A-1 were mixed uniformly in a mass ratio of 25:60:10:5 to obtain a mixed solvent, and then lithium hexafluorophosphate and lithium bisfluorosulfonyl imide were added to the mixed solvent, the content of lithium hexafluorophosphate was 10wt%, and the content of lithium bisfluorosulfonyl imide was 6wt%. Then, 3wt% of ethylene carbonate, 1wt% of ethylene sulfate, and 1wt% of compound B-1 were added thereto and mixed uniformly to obtain an electrolyte.
[0061] Preparation of positive electrode sheet: After lithium iron phosphate, Li5FeO4, acetylene black and polyvinylidene fluoride are mixed in a mass ratio of 95.7:1.5:1:1.8, NMP is added and stirred in a vacuum mixer until the system is uniform to obtain positive electrode slurry. The positive electrode slurry is evenly coated on aluminum foil, then dried at room temperature and transferred to an oven for drying, and the positive electrode sheet is obtained through cold pressing, trimming, cutting and slitting.
[0062] Preparation of negative electrode sheets: The negative electrode active materials are graphite and silicon-carbon composites, and the mass ratio of the silicon-carbon composite to graphite is, for example, 3:97. The negative electrode active materials, conductive carbon black, sodium carboxymethyl cellulose and styrene-butadiene rubber are mixed in a mass ratio of 96.5:1:1:1.5, deionized water is added, and the mixture is mixed evenly under the action of a vacuum mixer to obtain a negative electrode slurry. The negative electrode slurry is coated on a copper foil, and then dried at room temperature and transferred to an oven for drying. After cold pressing, trimming, cutting and slitting processes, a negative electrode sheet is obtained.
[0063] Selection of diaphragm: Polyethylene with a thickness of 9 μm is used as the base membrane.
[0064] Preparation of battery: The positive electrode sheet, separator, and negative electrode sheet are wound in sequence, and the separator is placed between the positive electrode sheet and the negative electrode sheet to play an isolating role, thereby obtaining a bare cell. Then the bare cell is placed in an aluminum-plastic film, dried, injected with electrolyte, and sealed. After at least vacuum packaging, standing, formation, and shaping processes, a lithium-ion battery is obtained.
[0065] Example 2
[0066] In the electrolyte, the mass ratio of EC, EMC, DMC and compound A-1 is 20:60:10:10, and the other steps are consistent with Example 1.
[0067] Example 3
[0068] In the electrolyte, the mass ratio of EC, EMC, DMC and compound A-1 is 20:60:10:10, compound B-1 is replaced by compound B-2 and compound B-3, the content of compound B-2 is 0.5wt%, the content of compound B-3 is 0.5wt%, and the other steps are consistent with Example 1.
[0069] Example 4
[0070] In the electrolyte, the mass ratio of EC, EMC, DMC and compound A-1 is 20:60:10:10, compound B-1 is partially replaced by compound B-4, the content of compound B-1 is 0.5wt%, the content of compound B-4 is 0.5wt%, and the other steps are consistent with Example 1.
[0071] Example 5
[0072] In the electrolyte, the mass ratio of EC, EMC, DMC and compound A-1 is 20:60:10:10, the second additive is compound B-1 and compound B-4, the content of compound B-1 is 1.5wt%, the content of compound B-4 is 1.5wt%, and the other steps are consistent with Example 1.
[0073] Example 6
[0074] In the electrolyte, the mass ratio of EC, EMC, DMC and compound A-1 is 20:60:10:10, the content of compound B-1 is 3wt%, and the other steps are consistent with Example 1.
[0075] Example 7
[0076] In the electrolyte, the mass ratio of EC, EMC, DMC and compound A-1 is 20:60:10:10, the content of compound B-1 is 5wt%, and the other steps are consistent with Example 1.
[0077] Example 8
[0078] In the electrolyte, compound A-1 is replaced by compound A-2, the mass ratio of EC, EMC, DMC and compound A-2 is 20:60:10:10, compound B-1 is replaced by compound B-2, the content of compound B-2 is 1wt%, and the other steps are consistent with Example 1.
[0079] Example 9
[0080] In the electrolyte, compound A-1 is replaced by compound A-3, the mass ratio of EC, EMC, DMC and compound A-3 is 20:60:10:10, compound B-1 is replaced by compound B-2, the content of compound B-2 is 1wt%, and the other steps are consistent with Example 1.
[0081] Example 10
[0082] In the electrolyte, compound A-1 is replaced by compound A-4, the mass ratio of EC, EMC, DMC and compound A-4 is 20:60:10:10, compound B-1 is replaced by compound B-2, the content of compound B-2 is 1wt%, and the other steps are consistent with Example 1.
[0083] Embodiment 11
[0084] In the electrolyte, compound A-1 is replaced by compound A-5, the mass ratio of EC, EMC, DMC and compound A-5 is 20:60:10:10, compound B-1 is replaced by compound B-2, the content of compound B-2 is 1wt%, and the other steps are consistent with Example 1.
[0085] Example 12
[0086] In the electrolyte, compound A-1 is replaced by compound A-5 and compound A-6, the mass ratio of EC, EMC, DMC, compound A-5 and compound A-6 is 20:60:10:5:5, compound B-1 is replaced by compound B-2, the content of compound B-2 is 1wt%, and the other steps are consistent with Example 1.
[0087] Embodiment 13
[0088] In the electrolyte, compound A-1 is replaced by compound A-4 and compound A-5, the mass ratio of EC, EMC, DMC, compound A-4 and compound A-5 is 20:60:10:5:5, compound B-1 is replaced by compound B-2, the content of compound B-2 is 1wt%, and the other steps are consistent with Example 1.
[0089] Embodiment 14
[0090] When preparing the positive electrode plate, the lithium supplement Li5FeO4 is replaced by Li2NiO2, and the other steps are consistent with Example 1.
[0091] Embodiment 15
[0092] When preparing the positive electrode plate, the lithium supplement Li5FeO4 is replaced by Li6CoO4, and the other steps are consistent with Example 1.
[0093] Comparative Example 1
[0094] Preparation of electrolyte: In an argon glove box with an oxygen content of 0.1ppm and a water content of 0.1ppm, EC, EMC and DMC were mixed at a mass ratio of 30:60:10 to obtain a mixed solvent, and then lithium hexafluorophosphate and lithium bisfluorosulfonyl imide were added to the mixed solvent, the content of lithium hexafluorophosphate was 10wt%, and the content of lithium bisfluorosulfonyl imide was 6wt%. Then, 3wt% of ethylene carbonate and 1wt% of ethylene sulfate were added thereto and mixed to obtain an electrolyte.
[0095] When preparing the positive electrode plate, the lithium supplement Li5FeO4 is replaced by Li2NiO2, and the other steps are consistent with Example 1.
[0096] Comparative Example 2
[0097] Preparation of electrolyte: In an argon glove box with an oxygen content of 0.1ppm and a water content of 0.1ppm, EC, EMC and DMC are mixed uniformly in a mass ratio of 30:60:10 to obtain a mixed solvent, and then lithium hexafluorophosphate and lithium bisfluorosulfonyl imide are added to the mixed solvent, the content of lithium hexafluorophosphate is 10wt%, and the content of lithium bisfluorosulfonyl imide is 6wt%. Then, 3wt% of ethylene carbonate and 1wt% of ethylene sulfate are added thereto and mixed uniformly to obtain an electrolyte. The other steps are consistent with Example 1.
[0098] Comparative Example 3
[0099] Preparation of electrolyte: In an argon glove box with an oxygen content of 0.1ppm and a water content of 0.1ppm, EC, EMC and DMC were mixed at a mass ratio of 30:60:10 to obtain a mixed solvent, and then lithium hexafluorophosphate and lithium bisfluorosulfonyl imide were added to the mixed solvent, the content of lithium hexafluorophosphate was 10wt%, and the content of lithium bisfluorosulfonyl imide was 6wt%. Then, 3wt% of ethylene carbonate and 1wt% of ethylene sulfate were added thereto and mixed to obtain an electrolyte.
[0100] When preparing the positive electrode plate, the lithium supplement Li5FeO4 is replaced by Li6CoO4, and the other steps are consistent with Example 1.
[0101] Comparative Example 4
[0102] The second additive is not included in the electrolyte, and the other steps remain the same as those in Example 1.
[0103] Comparative Example 5
[0104] The electrolyte contained 1 wt % of compound B-1, and the other steps were the same as those in Comparative Example 2.
[0105] In the present invention, in Examples 1-15 and Comparative Examples 1-5, the components of the electrolyte in the lithium ion battery are shown in Table 1, and different electrolytes are used to prepare lithium ion batteries, and the performance of the lithium ion batteries is tested. The test results are shown in Table 2.
[0106] In one embodiment of the present invention, the test method of the low temperature DC impedance test is as follows: at 25°C, the lithium-ion battery is charged to 3.75V at a constant current of 1 / 3C, and then charged at a constant voltage to a current of 0.05C. Then the battery is discharged to 2.5V at a constant current of 1 / 3C. Repeat the above charging steps once, and the charging capacity is recorded as C0. The battery is discharged to (50%*C0) at a constant current of 1 / 3C. Then the battery is placed at -20°C and the initial voltage is recorded as U0. The battery is discharged at a constant current of 1C for 30s, and the terminal voltage is recorded as U1. DCR = (U0-U1) / (C0*1).
[0107] In one embodiment of the present invention, the test method of the initial DCR test at room temperature is as follows: at 25°C, the lithium-ion battery is charged to 3.75V at a constant current of 1 / 3C, and then charged to a current of 0.05C at a constant voltage. The battery is then discharged to 2.5V at a constant current of 1 / 3C. Repeat the above charging steps, and after recording the charging capacity as C0, the next charging capacity is recorded as C1. The battery is discharged to (50%*C1) at a constant current of 1 / 3C, and the initial voltage is recorded as U2. The battery is discharged at a constant current of 1C for 30s, and the terminal voltage is recorded as U3. Initial DCR at room temperature = (U2-U3) / (C1*1).
[0108] In one embodiment of the present invention, the test method of the high temperature storage test is as follows: the lithium-ion battery is stored at 60°C for 30 days (30D). The battery is then placed at 25°C and discharged to 2.5V at a 1 / 3C constant current, and then the battery is charged to 3.75V at a 1 / 3C constant current, and then charged to a current of 0.05C at a constant voltage. The battery is then discharged to 2.5V at a 1 / 3C constant current, and the discharge capacity is recorded as C2. The capacity recovery rate is (C2 / C1)*100%. Repeat the above charging steps, and the second charging capacity is recorded as C3. The battery is discharged to (50%*C3) at a 1 / 3C constant current, and the initial voltage is recorded as U4. The battery is discharged at a 1C constant current for 30s, and the terminal voltage is recorded as U5. DCR = (U4-U5) / (C4*1). DCR growth rate = (DCR after storage for 30 days-initial DCR) / initial DCR*100%. At the same time, record the volume V1 of the lithium-ion battery at 25°C before storage and the volume V2 at room temperature after storage at 60°C for 30 days. Volume expansion rate = (V2-V1) / V1*100%. In this embodiment, the operating voltage window of the lithium iron phosphate system is 2.5V to 3.75V. In other embodiments, when other positive electrode active materials are selected, the operating voltage window is adjusted according to the positive electrode active materials.
[0109] In one embodiment of the present invention, the lithium plating test (ALP) is to place the lithium ion batteries of Examples 1-15 and Comparative Examples 1-5 in a 25°C thermostat, and then charge them to 3.75V at a rate of 0.33C in a 25°C thermostat, and then charge them at a constant voltage to a current of 0.05C. Then discharge the battery to 2.5V at a constant current of 1 / 3C, and then continue to discharge to 2.0V at 0.1C, and record the discharge capacity at this time as C6, then charge to 3.75V at a rate of 0.33C in a 25°C thermostat, and then discharge to 90%*C6 at 0.33C, adjust the thermostat temperature to -20°C, leave for 3h, and then charge to 70% battery capacity (State of Charge, SOC) at a rate of 1.2C, and then adjust to 80% SOC. Then charge at 0.33C to 3.75V, and then charge at a constant current of 0.05C to 3.75V, adjust the temperature of the thermostat to 25℃, and leave it for 3 hours. Finally, discharge at 0.33C to 2.0V, and repeat the above lithium deposition process for 10 cycles. Finally, the battery cell is fully charged and the interface is disassembled offline to check the lithium deposition.
[0110] Table 1. Components of the electrolyte in Examples 1-15 and Comparative Examples 1-5
[0111]
[0112] Table 2. Performance of lithium-ion batteries in Examples 1-15 and Comparative Examples 1-5
[0113]
[0114] Please refer to Table 1 and Table 2. Comparison of Example 1, Comparative Example 2, Comparative Example 4 and Comparative Example 5 shows that when the first additive and the second additive are not added to the electrolyte, the low-temperature and normal-temperature impedance of the lithium-ion battery is high, the high-temperature storage DCR growth rate is high, and the high-temperature storage volume expansion rate is large, and there is a lithium precipitation problem, indicating that the safety of the lithium-ion battery is poor. When the first additive is added to the electrolyte and the second additive is not added, relative to Comparative Example 2, the low-temperature and normal-temperature impedance of the lithium-ion battery is reduced, the high-temperature storage DCR growth rate and the high-temperature storage volume expansion rate are reduced, and there is no lithium precipitation problem, indicating that the first additive can effectively inhibit gas production and improve the fast charging performance and low-temperature discharge performance of the lithium-ion battery. When the first additive is not added to the electrolyte and the second additive is added, relative to Comparative Example 2, the low-temperature and normal-temperature impedance of the lithium-ion battery is reduced, the high-temperature storage DCR growth rate is reduced, and the high-temperature storage volume expansion rate is large, and there is no lithium precipitation problem, indicating that the second additive can increase the lithium borate, lithium fluoride and lithium carbonate substances in the interface film, improve the ability to conduct lithium ions, and reduce impedance. When the first additive and the second additive are used at the same time, the low-temperature and room-temperature impedance of the lithium-ion battery are reduced, the high-temperature storage DCR growth rate is reduced, and the high-temperature storage volume expansion rate is greatly reduced, and there is no lithium precipitation problem. This shows that the first additive and the second additive are used together to reduce the DC impedance of the lithium-ion battery, inhibit the gas production caused by the lithium supplement, reduce the loss of active lithium, and increase the low-temperature lithium precipitation window, thereby improving the high and low temperature performance of the lithium-ion battery.
[0115] Please refer to Table 1 and Table 2. By comparing Examples 1-15 and Comparative Examples 1-3, it can be seen that the low-temperature and room-temperature impedances of lithium-ion batteries are reduced, the high-temperature storage DCR growth rate is reduced, and the high-temperature storage volume expansion rate is greatly reduced, and there is no lithium precipitation problem, which means that the first additive can be oxidized and ring-opened polymerized on the positive electrode side to form a film, and at the same time, it has a high dielectric constant and replaces part of EC as a solvent to maintain the overall electrolyte conductivity at a high level. At the same time, it reduces the oxidative decomposition of cyclic ester EC by the active oxygen released by the lithium supplement in the positive electrode plate. The second additive can reduce the high impedance brought by the first additive to a certain extent, and the synergistic effect improves the gas production in the lithium supplement and increases the low-temperature lithium precipitation window.
[0116] Please refer to Table 1 and Table 2. By comparing Examples 1 and 2, it can be seen that when the content of the first additive is increased, the low-temperature and room-temperature impedances of the lithium-ion battery are reduced, the high-temperature storage DCR growth rate is reduced, and the high-temperature storage volume expansion rate is further reduced, and the high-temperature capacity recovery rate is slightly increased, indicating that the first additive is used to replace part of the EC, and the viscosity of the electrolyte is reduced without affecting the overall conductivity. At the same time, the film-forming consumption of the first additive is also smaller. When the content of the first additive is greater than 5wt%, the lithium sulfonate component in the film-forming component of the first additive is higher, and the lithium ion conductivity is strong, which helps to reduce the interface impedance and other properties.
[0117] Refer to Table 1 and Table 2. Comparison of Examples 2-7 shows that the second additives with different structures can improve the performance of lithium-ion batteries, and the improvement effect is similar when the content is the same, indicating that the second additives with different structures can improve the performance of lithium-ion batteries. As the content of the second additive increases, the reduction of interface impedance and the improvement of low-temperature lithium precipitation reach a threshold. Considering the above, the maximum amount of the second additive is recommended to be 5wt%.
[0118] Please refer to Table 1 and Table 2. By comparing Examples 7-13, it can be seen that the first additives with different structures can improve the performance of lithium-ion batteries, and the improvement effect is similar when the content is the same, indicating that the first additives with different structures can improve the performance of lithium-ion batteries. By comparing Examples 1, 14-15, it can be seen that for different lithium supplements, the first additive and the second additive process can effectively inhibit the gas production caused by the lithium supplement and improve the low-temperature lithium precipitation window.
[0119] The present invention also provides an electronic device, the electronic device includes at least one of the above-mentioned lithium-ion batteries, and the lithium-ion battery is used to provide electrical energy. Among them, the electronic device can be a vehicle, a mobile phone, a portable device, a laptop computer, a ship, a spacecraft, an electric toy and an electric tool, etc. In one embodiment of the present invention, the vehicle is, for example, a new energy vehicle, and the new energy vehicle can be a pure electric vehicle, a hybrid vehicle or an extended-range vehicle, etc. Spacecraft include airplanes, rockets, space shuttles and spacecrafts, etc. Electric toys include fixed or mobile electric toys, such as game consoles, electric car toys, electric ship toys and electric airplane toys, etc. Electric tools include metal cutting electric tools, grinding electric tools, assembly electric tools and railway electric tools, such as electric drills, electric grinders, electric wrenches, electric screwdrivers, electric hammers, impact drills, concrete vibrators and electric planers, etc. The electronic device includes the above-mentioned lithium-ion battery, so the advantages of the above-mentioned lithium-ion battery are included, which will not be elaborated here.
[0120] In summary, the present invention proposes a lithium-ion battery electrolyte and its application. Through the combined use of a first additive and a second additive, the oxidation side reaction at the solid-liquid interface can be reduced, the stability of the electrochemical window can be improved, the gas production can be effectively suppressed, the viscosity of the electrolyte can be reduced, and the fast charging performance and low-temperature discharge performance of the lithium-ion battery can be improved. The DC impedance of the lithium-ion battery can be reduced, the loss of active lithium can be reduced, and the low-temperature lithium precipitation window can be improved. The stability of the interface film can be improved, thereby improving the electrochemical performance. The charge and discharge efficiency and energy density of the lithium-ion battery can be improved, the high and low temperature performance of the battery can be enhanced, and the safety performance of the battery can be improved.
[0121] The above description is only a preferred embodiment of the present application and an explanation of the technical principles used. Those skilled in the art should understand that the scope of the invention involved in the present application is not limited to the technical solution formed by a specific combination of the above-mentioned technical features, but should also cover other technical solutions formed by any combination of the above-mentioned technical features or their equivalent features without departing from the inventive concept, such as a technical solution formed by replacing the above-mentioned features with (but not limited to) technical features with similar functions disclosed in this application.
[0122] Except for the technical features described in the specification, the remaining technical features are known technologies to those skilled in the art. In order to highlight the innovative features of the present invention, the remaining technical features will not be described here in detail.
Claims
1. A lithium ion battery electrolyte, characterized in that: At least the following components are included: Non-aqueous solvents; Lithium salts; as well as Additives, the additives include a first additive and a second additive, the first additive has a structural formula of Formula A, and the second additive is selected from a compound having a structural formula of Formula B1 or Formula B2; Wherein, n1 and n2 are each independently any natural number from 1 to 3, and R1, R2, R3, R4, and R5 are each independently selected from -H, -F, C 1~6 Alkyl, C 1~6 Alkoxy, C 2~6 Alkenyl, C 2~6 Alkenyloxy, C 2~10 Alkynyl, C 2~10 Alkynyloxy, C 3~8 Cycloalkyl, C 3~8 Epoxyalkyl, C 6~12 Aryl, C 6~12 heteroaryl or carbonyl, trifluoromethyl, and C 2~6 Any one or a combination of ester groups.
2. The lithium ion battery electrolyte according to claim 1, characterized in that: At least one of R1 and R2 includes C 2~6 Alkenyl, C 2~10 Alkynyl, C 1~6 Alkoxy, C 2~6 Any one or a combination of ester group or -F.
3. The lithium ion battery electrolyte according to claim 1, characterized in that The first additive is selected from any one or a combination of the following compounds:
4. The lithium ion battery electrolyte according to claim 1, characterized in that: The second additive is selected from any one or a combination of the following compounds:
5. The lithium ion battery electrolyte according to claim 1, characterized in that: The content of the first additive in the electrolyte is 0.5 wt % to 20 wt %.
6. The lithium ion battery electrolyte according to claim 1, characterized in that: The content of the second additive in the electrolyte is 0.5 wt % to 5 wt %.
7. The lithium ion battery electrolyte according to claim 1, characterized in that: The additives also include a third additive, which is selected from at least one or more combinations of ethylene carbonate, 1,3-propane sultone, 1,3-propylene sultone, 2,4-butane sultone, methylene disulfonate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorophosphate, lithium difluorobisoxalatophosphate or vinyl sulfate.
8. The lithium-ion battery electrolyte according to claim 1, characterized in that: The non-aqueous solvent is selected from at least one or more of ethylene carbonate, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, propylene carbonate, ethyl acetate, methyl acetate, ethyl formate, propyl formate, propyl acetate, methyl propionate, ethyl propionate or propyl propionate.
9. The lithium ion battery electrolyte according to claim 1, characterized in that: The lithium salt is selected from at least one or more of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium perchlorate, lithium hexafluoroarsenate, lithium tetrafluoroborate, lithium bis(oxalato)borate or lithium difluorooxalatoborate, and the content of the lithium salt in the electrolyte is 5wt% to 25wt%.
10. A lithium ion battery, characterized in that: include: A positive electrode plate, wherein the positive electrode plate includes a lithium supplement, and the lithium supplement includes one or more of Li2NiO2, Li6CoO4 or Li5FeO4; Negative electrode; A diaphragm, disposed between the positive electrode sheet and the negative electrode sheet; An electrolyte, wherein the electrolyte is selected from the lithium-ion battery electrolyte according to any one of claims 1 to 9.
11. The lithium ion battery according to claim 10, characterized in that: The positive electrode plate includes a positive electrode active material, and the positive electrode active material includes at least one or more of lithium iron phosphate, a composite material of lithium iron phosphate and carbon, lithium manganese phosphate, a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon.
12. An electronic device, characterized in that: A lithium-ion battery comprising any one of claims 10-11.
Citation Information
Patent Citations
ESIPT luminescent material with high exciton utilization rate and preparation method and application thereof
CN113563325A
Lithium ion battery electrolyte, lithium ion battery and electrochemical equipment
CN118676437A
Lithium ion battery electrolyte and application thereof
CN118693348A
Electrolytic solution, electrochemical device, lithium ion secondary battery, and module
JP2019114418A
Organic electrolytic solution and lithium battery employing the same
KR1020090082780A
Cited By
Non-aqueous electrolyte, lithium ion battery, battery module, battery pack and electric device
CN122177937A